A guide to practical toxicology evaluation, prediction and risk - Woolley, Adam.; Woolley, Adam. (Boca Raton, Fla. : CRC Press, 2003)
Toxicology is a means to an important end: safety. The effective toxicologist begins with this in mind, and uses a clear understanding of safety as a relative concept, together with a rational view of the current safety evaluation paradigm to direct their work. Too often this approach is ignored or discouraged by traditional practice. This lucid, readable book encourages both experienced toxicologists, and those in training, to place toxicological investigation in such a framework. It looks at the importance of toxicological normality, reviews toxicity testing methods, and explores new and "alternative" methods of safety evaluation. The interpretation of toxicity findings in individual studies and data packages and the prediction of human-relevant hazards are reviewed, followed by an introduction to risk and how we perceive and assess risk in the light of known hazards and the probability of their occurrence. The final stage of the toxicological process - risk assessment and management - is reviewed with particular reference to the work place. The book is suitable for professional and student toxicologists as well as those from outside the field who require some knowledge of toxicological method and interpretation, for instance in occupational hygiene or medicine and veterinary surgery. - Back cover.
List of illustrations -- Preface -- Acknowledgements -- 1. Introduction to toxicology : the necessity of measurement -- 2. Normality : definition and maintenance -- 3. Determination of toxicity : basic principles -- 4. Determination of toxicity in in vitro -- 5. Determination : general and reproductive toxicology -- 6. determination : genotoxicity and carcinogenicity -- 7. Determinism : irritation and sensitisation -- 8. Determination : environmental toxicology and epidemiology -- 9. Interpretation -- 10. Prediction of hazard -- 11. Background to risk due to toxicity -- 12. Risk assessment in practice and setting exposure limits -- 13. Risk assessment and management in the workplace -- 14. Risk assessment : carcinogenicity; the environment; evolution and overview of risk assessment -- 15. The future of toxicity testing -- Appendix : useful websites -- Select glossary -- Notes -- Bibliography -- Index.
Includes bibliographical references (p. [311]-312) and index.
All Ages.
Keywords: Toxicology; Chemical models